2011
DOI: 10.1175/2010jamc2363.1
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric Radar Observation Operator for a Cloud Model with Spectral Microphysics

Abstract: The radar observation operator for computation of polarimetric radar variables from the output of numerical cloud models is described in its most generic form. This operator is combined with the Hebrew University of Jerusalem cloud model with spectral microphysics. The model contains 7 classes of hydrometeors and each class is represented by size distribution functions in 43 size bins. The performance of the cloud model and radar observation operator has been evaluated for the case of a hailstorm in Oklahoma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
159
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 45 publications
0
159
0
Order By: Relevance
“…Kumjian andRyzhkov (2008, p. 1944) pointed out that these ''small, wet hailstones are sensed as giant raindrops, characterized by very high Z DR .' ' Borowska et al (2011) and Ryzhkov et al (2011) accounted for these characteristics of melting hail in their polarimetric emulator by utilizing linear approximations between the aspect ratio of a dry hailstone and that of a raindrop into which it eventually melts, based on the laboratory investigations of RLP84, and by decreasing the width of the canting-angle distribution from 408-508 for dry graupel/ hail to 108 when completely melted. In our study, we follow an approach very similar to that of Ryzhkov et al (2011) for computing the aspect ratio and width of the canting-angle distribution for melting hail with the following main differences: 1) the linear decrease of the canting-angle distribution width is applied for water fractions between 0 and 0.5 and is set to 08 above that threshold, and 2) a value of 608 is used for completely dry hail.…”
Section: B Polarimetric Emulatormentioning
confidence: 99%
“…Kumjian andRyzhkov (2008, p. 1944) pointed out that these ''small, wet hailstones are sensed as giant raindrops, characterized by very high Z DR .' ' Borowska et al (2011) and Ryzhkov et al (2011) accounted for these characteristics of melting hail in their polarimetric emulator by utilizing linear approximations between the aspect ratio of a dry hailstone and that of a raindrop into which it eventually melts, based on the laboratory investigations of RLP84, and by decreasing the width of the canting-angle distribution from 408-508 for dry graupel/ hail to 108 when completely melted. In our study, we follow an approach very similar to that of Ryzhkov et al (2011) for computing the aspect ratio and width of the canting-angle distribution for melting hail with the following main differences: 1) the linear decrease of the canting-angle distribution width is applied for water fractions between 0 and 0.5 and is set to 08 above that threshold, and 2) a value of 608 is used for completely dry hail.…”
Section: B Polarimetric Emulatormentioning
confidence: 99%
“…However, the validation of the operator was limited to idealized cases at S-band only. Ryzhkov et al (2011) developed an advanced forward radar operator for a research cloud model with spectral microphysics able to simulate Z H , Z DR , LDR, and K dp . Scattering amplitudes of smaller particles are estimated with the Rayleigh approximation whereas the T-matrix method is used for larger hydrometeors.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this objective includes the development of data assimilation techniques to ingest dual-polarimetric radar data into convection-permitting NWP models. A necessary step for data assimilation was the development of a flexible, fully featured radar simulator of polarimetric radar variables (e.g., Jung et al 2008;Pfeifer et al 2008;Ryzhkov et al 2011) within the mesoscale, nonhydrostatic atmospheric model Méso-NH (Lafore et al 1998) to enable direct comparisons between model-simulated and observed polarimetric radar variables. The newly developed polarimetric radar simulator, which is based on the conventional radar simulator of Caumont et al (2006), calculates electromagnetic wave propagation and scattering at S, C, and X bands and considers beam propagation effects, such as (differential) attenuation and phase shift, and beam refraction and broadening.…”
Section: Toward the Assimilation Of New Radar Observations Dual-polamentioning
confidence: 99%
“…This signature is the result of cross coupling between orthogonally polarized waves when the radar is operating in simultaneous transmission and reception (STAR) mode. Radial streaks in Z DR and Φ DP at heights of 7-10 k m have been attributed to ice crystals oriented by electrostatic fields in regions of storm electrification (Ryzhkov and Zrnić 2007;Hubbert et al 2010). While these depolarization signatures, which can cause bias in Z DR , are usually considered undesirable (Hubbert et al 2010), they can also be used as an indicator of strong electrification and thus be used as an opportunity to detect charged ice particles in absence of a lightning detection sensor.…”
mentioning
confidence: 99%